Independently Rotating Wheels with Induction Motors for High-Speed Trains - B. Liang; S. D. Iwnicki (Journal of Control Science and Engineering)
Railway vehicles with conventional wheelsets often experience problems of lateral instabilities or severe wear when running at high speed. The use of an independently rotating wheelset (IRW) can potentially eliminate the cause of wheelset hunting and reduce wheel wear as the mechanical feedback mechanism causing the problem is decoupled. This paper presents an investigation into the design of a novel induction motor configuration and controller for IRW in order to provide the stability required to satisfy the performance requirements for railway vehicles. A computer model of the mechanical and electrical parts of the system was developed. Simulation and experiments of the wheelsets with active driving motor control have demonstrated that a wheelset with independently driven wheels has a good stability performance over a traditional wheelset. Controllers with indirect field orientation control for dynamic control of an induction motor have shown to be suitable for this application in both its response and its controllability.